2005
DOI: 10.1142/s0219525905000531
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical and Topological Study of the Protein–protein Interaction Networks

Abstract: We employ the random graph theory approach to analyze the protein–protein interaction database DIP. Several global topological parameters are used to characterize the protein–protein interaction networks (PINs) for seven organisms. We find that the seven PINs are well approximated by the scale-free networks, that is, the node degree cumulative distribution P cum (k) scales with the node degree k (P cum (k) ~ k-α). We also find that the logarithm of the average clustering coefficient C ave (k) scales with k (C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…We notice that the C"ve(k) plot for the fruit fly PIN exhibits a rather flat plateau for a large range of k, and it falls rapidly for large k. In addition, the clustering coefficient C for fruit fly is the smallest among the seven species, where one would expect a large C value for hierarchical network model. These results 26 For the other four species (C. elegans, H. pylori, H. sapiens and M. musculus) our results indicate that their C me (k) values decrease with k (i.e. 0.49^/7^0.66) and have a less significant coefficients of determination.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…We notice that the C"ve(k) plot for the fruit fly PIN exhibits a rather flat plateau for a large range of k, and it falls rapidly for large k. In addition, the clustering coefficient C for fruit fly is the smallest among the seven species, where one would expect a large C value for hierarchical network model. These results 26 For the other four species (C. elegans, H. pylori, H. sapiens and M. musculus) our results indicate that their C me (k) values decrease with k (i.e. 0.49^/7^0.66) and have a less significant coefficients of determination.…”
Section: Resultssupporting
confidence: 72%
“…Regression and correlation results of the logarithm of C me (k) vs. the logarithm of k plots (P, r 2 and p-value), the clustering coefficients C for the seven species, and the C values from Ref. 26. The results indicate that C ave (k) decreases with k for the seven species, as illustrate in Table 4 and Figures 3, and 4.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…assortative/disassortative, small world etc., of molecular networks [9][10] . For instance, it has been shown that protein-protein interaction networks are well described by scale-free networks or hierarchical network models 11 .…”
mentioning
confidence: 99%